The Impact of Inward FDI on the Performance of Chinese Manufacturing Firms - Buckley, Peter J.; Clegg, Jeremy; Wang, Chengqi (Journal of International Business Studies, 2002)
Using detailed cross-section data for 1995, non-Chinese MNEs are found to generate technological and international market access spillover benefits for Chinese firms, while overseas Chinese investors confer only market access benefits. State-owned enterprises reap no benefits, and indeed receive negative spillovers from overseas investors, in marked contrast to the positive spillovers gained by collectively-owned firms. These findings underline the importance of reform in state-owned enterprises to raise the absorptive capacity of the Chinese domestically-owned sector.